The Impact of Smoking on Post-Clopidogrel Platelet Reactivity in Patients With Acute Myocardial Infarction - Cho, Jung-Hyun (The Korean Society of Cardiology, 2010)
BACKGROUND AND OBJECTIVES: Smoking increases inhibition of clopidogrel-induced platelet reactivity in patients undergoing elective coronary stenting. However, an association between pre-admission smoking (PS) and post-clopidogrel platelet reactivity in patients with acute myocardial infarction (AMI) has not been determined. SUBJECTS AND METHODS: Study cohorts were recruited from a pool of patients at our hospital who were undergoing coronary stenting for AMI (n=134). Immediately after arrival at the emergency room (ER), all patients received a 600 mg loading dose of clopidogrel followed by a maintenance dose of 75 mg/day. Platelet aggregation was measured with light transmittance aggregometry (LTA) after addition of 5 or 20 µmol/L adenosine diphosphate (ADP). RESULTS: Maximal platelet aggregation (Agg(max)) was lower in PS patients after 5 µmol/L ADP (43.6±15.7% vs. 48.4±12.5%, p=0.096) and 20 µmol/L ADP stimuli (56.2±15.6% vs. 61.3±11.6%, p=0.073) compared with non-smoking (NS) patients. However, there were no differences in 5 µmol/L (42.6±16.3% vs. 43.8±15.6%, p=0.776) and 20 µmol/L ADP-induced Agg(max) (54.8±14.3% vs. 56.5±15.9%, p=0.692) between PS patients <0.5 pack/day and ≥0.5 pack/day. Although more PS patients met the criteria for low post-clopidogrel platelet reactivity (LPPR) (≤37%; the lowest quartile of 5 µmol/L ADP-induced Agg(max)) than NS patients (30.9% vs. 13.5%, p=0.048), advancing age was the only independent predictor of LPPR {odds ratio (OR) 0.960, 95% confidence interval (CI) 0.929 to 0.993, p=0.019}. CONCLUSION: PS is significantly not associated with decreased residual platelet reactivity in AMI patients.